2021
DOI: 10.1007/s11581-021-04023-y
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxations and ion transport study of NaCMC:NaNO3 solid polymer electrolyte films

Abstract: Na+ ion-conducting solid polymer electrolyte (SPE) of sodium salt of carboxymethyl cellulose (NaCMC) doped with sodium nitrate (NaNO3) was developed by solution casting method. FTIR technique confirmed the formation of hydrogen bonding between $$ {NO}_3^{-} $$ NO 3 − anion and functional groups of NaCMC. XRD study revealed the low degree of crystallinity that reduced upon doping. Impedance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The finding is comparable to other Na-based electrolytes e.g. PVA-NaI-Gly (0.98) [ 41 ], PVA-NaI (0.954–0.974) [ 42 ], and CMC-NaNO 3 (0.97) [ 43 ].
Figure 4 Polarization curve of CS-NaI-Gly electrolyte at 0.2 V.
…”
Section: Resultssupporting
confidence: 74%
“…The finding is comparable to other Na-based electrolytes e.g. PVA-NaI-Gly (0.98) [ 41 ], PVA-NaI (0.954–0.974) [ 42 ], and CMC-NaNO 3 (0.97) [ 43 ].
Figure 4 Polarization curve of CS-NaI-Gly electrolyte at 0.2 V.
…”
Section: Resultssupporting
confidence: 74%
“…From Fig. 8b, there are no relaxation peaks in the plot of ′′ against log ω suggesting that the rise in dc conductivity is attributed to an increase in ion density rather than a structural relaxation process related to the reorientation of the dipoles in the system or the segmental relaxation of the polymer chains (Shetty et al 2021a). It is observed that both ′ and ′′ increase with salt concentration and is highest for S30 sample.…”
Section: Dielectric Studymentioning
confidence: 89%
“…From Figure 8B, a relaxation peak can be seen. This suggests that the increase in conductivity may be associated with an increase in carrier concentration and/or the structural relaxation phase, such as the realignment of dipoles in the polymer system 50 . The structural relaxation could be attributed to the side chain motion of Na‐CMC, that is, OCH2COONa 51 .…”
Section: Resultsmentioning
confidence: 99%